1994
DOI: 10.1029/94gl02459
|View full text |Cite
|
Sign up to set email alerts
|

Freezing temperatures of H2SO4/HNO3/H2O mixtures: Implications for polar stratospheric clouds

Abstract: The freezing temperatures of H2SO4/HNO3/H2O mixtures were systematically documented. Nitric acid was found to affect freezing significantly. Measurements show that nitric acid can cause substantial supercooling over a broad composition range. However, some ternary compositions, like to those in polar stratospheric clouds (PSCs), have high freezing temperatures. The freezing of PSC particles could be controlled by the temperature and vapor pressure of both nitric acid and water in a non‐linear way. Formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Nevertheless, explanations for NAT formation processes above T ICE have also been invoked, such as formation of amorphous solid particles at temperatures above T ICE (type 1c PSC) and subsequent cystallization upon warming [ Tabazadeh and Toon , 1996]; or direct NAT formation on STS solutions either when strong mesoscale temperature fluctuations lead the droplet composition close to the stoichiometry of NAT [ Meilinger et al , 1995; Song , 1994] or when temperature dwells long enough inside a well‐defined “nucleation window” [ Tabazadeh et al , 2001]. There is also a suggestion for heterogeneous freezing in the presence of suitable freezing nuclei [ Drdla et al , 2002].…”
Section: Microphysical Simulationsmentioning
confidence: 99%
“…Nevertheless, explanations for NAT formation processes above T ICE have also been invoked, such as formation of amorphous solid particles at temperatures above T ICE (type 1c PSC) and subsequent cystallization upon warming [ Tabazadeh and Toon , 1996]; or direct NAT formation on STS solutions either when strong mesoscale temperature fluctuations lead the droplet composition close to the stoichiometry of NAT [ Meilinger et al , 1995; Song , 1994] or when temperature dwells long enough inside a well‐defined “nucleation window” [ Tabazadeh et al , 2001]. There is also a suggestion for heterogeneous freezing in the presence of suitable freezing nuclei [ Drdla et al , 2002].…”
Section: Microphysical Simulationsmentioning
confidence: 99%
“…Whether this occurs under stratospheric conditions is uncertain. Some studies have concluded that the HNO 3 content does promote freezing [ Molina et al , 1993; Beyer et al , 1994; Song , 1994; Iraci et al , 1995; Bertram and Sloan , 1998a, 1998b; Salcedo et al , 2001] but others have found no freezing until below the ice frost point [ Koop et al , 1995, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Stratospheric sulfate aerosols (SSAs) affect the composition of the upper atmosphere through heterogeneous chemical reactions, as well as serving as nucleation sites for polar stratospheric clouds, or PSCs [Tolbert, 1994]. Recently, significant research has been aimed at answering pressing questions concerning the microphysics of PSCs and their precursors, SSAs [Turco and Hamill, 1992;Luo et al, 1992; van Doren et al, 1991; Watson et al, 1990;Dye et al, 1992;Anthony et al, 1995;Larsen, 1994;Beyer et al, 1994;Song, 1994;Tabazadeh and Toon, 1995;Luo et al, 1994;Jensen et al, 1991;Koop et al, 1995]. Several studies have attempted to determine freezing points for bulk sulfuric acid/water solutions, since the physical state of the aerosol will no doubt affect both the rate of heterogeneous reactions and the process of PSC formation.…”
Section: Introductionmentioning
confidence: 99%